THEORETICAL AND PRACTICAL ASPECTS OF ELICITION AND EVALUATION OF SCHOOL EDUCATION QUALITY - N. Y. Yerganova; L. V. Kolyasnikova; Y. V. Igonina (Obrazovanie i Nauka, 2015)
The paper considers one of the main theoretical and practical pedagogical problems of education quality assessment. The quality measurement depends on successful identification of genuine (scientific) and false diagnostic methods; the process becomes even more complicated in case of latent variables. As a solution, the authors recommend the Rasch measurement model for identifying an integral indicator of education quality. The method in question involves development, approbation and analysis of diagnostic materials, as well as mathematical and statistical data processing based on specialized computer software. The paper describes the advantages and theoretical potential of the Rasch method, and emphasizes its capacity for solving the key problem of quality modeling – i.e. suitability and utility of indicator variables for the given research.